Mechanisms underlying apathy in Parkinson's disease. (26th February 2015) - Muhammed, Kinan; Manohar, Sanjay; Husain, Masud
Abstract: Background: Apathy is a common syndrome observed in many neurological conditions, including in up to 70% of patients with Parkinson's disease. Mechanisms underlying apathy are poorly understood and clinically we lack robust, objective detection methods. We aimed to address this using novel objective measures of motivation and reward sensitivity in relation to apathy in patients with Parkinson's disease. Methods: Saccadic velocity and pupil modulation by reward were used as objective metrics of motivation in patients with Parkinson's disease. In addition, differences in reward sensitivity in patients off medication were compared with those on medication, and assessed in relation to apathy. 20 patients with idiopathic Parkinson's disease and 21 healthy participants were recruited. Patients were tested in counterbalanced sessions, on and off dopaminergic medication. Participants were asked to make saccadic eye movements for different monetary rewards, with eye position, velocity, and pupil diameter monitored with an infrared eye tracker. Faster initiation of saccades received a greater proportion of rewards. Apathy was indexed by Lille Apathy Rating Scale (LARS) scores. Findings: Healthy controls and patients on medication demonstrated an increase in saccadic peak velocity as reward magnitude increased (an increase by 41 deg/s [SE 20] p<0·0001, and 22·5 [4·7] p<0·0001, respectively). This reward sensitivity was lost in patients off medication (5·2 [3·2], p=0·117). In all groups, pupil diameter dilated more with larger rewards (p<0·05). In Parkinson's diease, pupil reward sensitivity was greater in patients on medication than off medication, but not statistically so (p=0·06). A median split of patients on medication into high motivated and low motivated groups based on LARS scores revealed a significant interaction between motivation level and rewards for saccadic peak velocity ( F 2, 18 =5·153, p=0·049), with the apathetic (low motivation) group exhibiting less reward sensitivity in saccadic peak velocity. Interpretation: These findings demonstrate that saccadic velocity and pupil diameter are affected by reward magnitude and that the degree of modulation varies with motivation levels across individuals. These indices provide a novel behavioural measure for probing disorders of motivation in neurological disorders such as Parkinson's disease. Dopaminergic medication might be an effective treatment for apathy by increasing reward sensitivity, independent of effects on motor control. Funding: Wellcome Trust.